BRIDGING EFL LEARNERS’ TARGET LANGUAGE KNOWLEDGE DISCREPANCY WITH THE SUPPORT OF CRITICAL CULTURAL AWARENESS - Kristian Florensio Wijaya (Magister Scientiae, 2024)
It has been a long-standing issue that EFL learners are required to consistently showcase gratifying target language performances, competencies, and achievements while taking part in a wide variety of second language learning activities without being prepared well with suitable and authentic learning materials. In response to this aforesaid issue, second language educators need to immerse EFL learners into critical cultural awareness to make them become more efficient target language users. This present small-scale library study was projected to profoundly investigate the way critical cultural awareness can bridge globalized EFL learners’ target language knowledge discrepancy in actual second language learning contexts. To do so, the researcher conducted an in-depth thematic analysis of the previously generated research results addressed by 20 critical cultural awareness studies published worldwide. Concerning the specifically-obtained research results, critical cultural awareness can potentially become one of the worthwhile strategies to be further applied in nowadays second language circumstances by which EFL learners foster their target language competencies to the desired outcomes and transform into more skillful target language users.